2021
DOI: 10.1186/s40545-021-00334-7
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of nursing mothers’ and young people’s access to proprietary and patent medicine vendors’ services in rural communities of south-eastern Nigeria: implication for review of national drug policy

Abstract: Background Patent and proprietary medicine vendors (PPMVs) form part of the informal healthcare system and are the first point of call for 75% of Nigerians who live in rural and underserved areas where there is limited access to healthcare services. This group of healthcare providers are located close to communities and are easily accessible to the people. This study seeks to determine how PPMVs influence access to medicines among nursing mothers and young people and how this progresses South E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Similarly, a study from Kogi and Kwara states in Nigeria reported that headache, fever, and cough accounted for over 70% of services utilized among PMVs [ 15 ]. In southeast Nigeria, antimalaria services accounted for 95% of services used by nursing mothers and young people [ 16 ], while in another study in Nigeria, cough and malaria were highlighted as leading presenting ailments among PMVs and CPs, followed by STI [ 17 ]. Given that malaria, pneumonia, diarrhea, and respiratory infections are the leading causes of under-five deaths in Nigeria, engaging PMVs and CPs to identify, refer, or treat these common conditions in line with national policy and guidelines and, based on these utilization patterns, is urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study from Kogi and Kwara states in Nigeria reported that headache, fever, and cough accounted for over 70% of services utilized among PMVs [ 15 ]. In southeast Nigeria, antimalaria services accounted for 95% of services used by nursing mothers and young people [ 16 ], while in another study in Nigeria, cough and malaria were highlighted as leading presenting ailments among PMVs and CPs, followed by STI [ 17 ]. Given that malaria, pneumonia, diarrhea, and respiratory infections are the leading causes of under-five deaths in Nigeria, engaging PMVs and CPs to identify, refer, or treat these common conditions in line with national policy and guidelines and, based on these utilization patterns, is urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…(PM News Nigeria, 2021). Again, since private medical service providers are viewed as superior alternatives to public facilities, given these harsh realities of public hospitals, the majority of Nigerians are progressively choosing to use their services (Uneke et al, 2021). Despite the fact that private healthcare facilities are presumably superior to public ones, low-income Nigerians are unable to receive healthcare due to the exorbitant expense of private medical treatment.…”
Section: Introductionmentioning
confidence: 99%